Antimicrobial analysis of chlorhexidine gel and intracanal medicaments against microorganisms inoculated in root canals - Valera, M. C.; Salvia, A. C.; Maekawa, L. E.; Camargo, S. E.; Carvalho, C. A.; Camargo, C. H.; Koga-Ito, C. Y. (My University, 2010)
The aim of this paper was to evaluate the antimicrobial activity of 2% chlorhexidine gel (CLX) associated with various intracanal medicaments against Candida albicans and Enterococcus faecalis inoculated in root canals. Thirty six human single-rooted teeth were contaminated with C.albicans and E.faecalis. The canals were instrumented using 2% CLX gel and were divided into three groups according to the intracanal medicaments (ICM) used. Group 1: calcium hydroxide paste [Ca(OH)], Group 2: 2% chlorhexidine gel (CLX) and Group 3: 2% CLX gel + Ca(OH). The root canal collections were performed after 21 days of contamination (control collection), after instrumentation (1st collection), after 14 days of intracanal medicament (2nd collection) and 7 days after medicament removal (3rd collection). The microbiological samples were plated in culture media and incubated for 48 hours. The results were submitted to Kruskal-Wallis test (P ≤ 0.05). It was verified that the instrumentation with CLX reduced the number of CFU/ml significantly when compared with the confirmation collection (control). However, the use of the ICM was only capable to eliminate completely the microorganisms in the root canals without difference statistics between them. Although the use of 2% chlorherixidine gel reduces the number of microorganisms significantly, only the ICM calcium hydroxide and calcium hydroxide associated with chlorhexidine are able to eliminate these microorganisms completely.
Keywords: calcium hydroxide; chlorhexidine; chlorhexidine gluconate; drug derivative; bacterial load; Candida albicans; comparative study; dental equipment; drug effect; drug potentiation; Enterococcus faecalis; equipment; evaluation; gel; growth, development and aging; human; in vitro study; isolation and purification; microbiological examination; microbiology; tooth pulp; Bacterial Load; Calcium Hydroxide; Chlorhexidine; Dental Instruments; Dental Pulp Cavity; Drug Synergism; Equipment Contamination; Gels; Humans; Microbial Sensitivity Tests